Association of PARP1 Gene Single Nucleotide Polymorphisms with Papillary Thyroid Carcinoma in The Iraqi population (Iraqi Journal of Science, 2024)
Thyroid carcinoma incidence is increasing year after year and ranking second among top ten cancers in Iraq, especially among women, and this increased the requirement for the improvement of the molecular detection accuracy because of its potential role in the early detection. Two single nucleotide polymorphisms (rs1136410, A>G and rs1805414, A>G) in PARP1 gene were found to be associated with thyroid carcinoma risk in several genome wide association studies, therefore, this is a case-control study that was carried out to identify whether these polymorphisms are associated with papillary thyroid carcinoma risk in Iraqi population. The Association was investigated in one hundred and one papillary thyroid carcinoma patients (11 male and 90 female) with ages (22-65), and one hundred and two controls (16 male and 86 female) with ages (21-67), using quantitative PCR-high resolution melting technique. The results showed that there is a strong association between both of rs1136410and rs1805414 with papillary thyroid carcinoma, the allele G was significantly associated with the disease as a risk factor in both variations (p<0.0001, odd ratio(OR): 4.9635, 95% confidence interval(CI): 3.2179-7.6560) in rs1136410, and (P<0.0001, odd ratio(OR): 3.1620, 95% confidence interval (CI): 2.0997-4.7619) in rs1805414. while the allele A represents a protective factor in both variations (OR=0.2015 and 0.3163 respectively). In conclusion, the allele G in both rs1136410 and rs1805414 in the PARP1 gene is strongly associated with papillary thyroid carcinoma in the Iraqi population.